Physicochemical Evaluation of Seeds and Oil of Nontraditional Oil Seeds - Adam Ismail Ahmed; Awad Mohammed Babeker; Ahmed Mohammed Ahmed Elamin; Elshiekh Awadelkarim Ibrahim (Turkish Journal of Agriculture: Food Science and Technology)
The present work was conducted in the Laboratory of Biochemistry and Food science department, Faculty of Natural Resources and Environmental Studies, University of Kordofan, in order to evaluate some nontraditional oil seeds these are i.e. Marula (Sclerocarya birrea), Roselle (Hibiscus sabdariffa L.) seeds and Christ’s thorn (Zizyphus spina-christi) seeds. The seeds of the roselle and Christ’s thorn fruits were procured from Elobeid local market, North Kordofan State, while marula fruits were obtained from Elnuhod, West Kordofan State. The proximate composition of the seeds, cake and christ’s thorn pulp was done. Some chemical and physical properties were performed for the extracted oil. The results revealed that proximate composition of the seeds and cake differ statistically among the studied materials. Significant differences were observed among the oil extracted from these species; moreover, these oils differ significantly in color and viscosity only.